Supporting countries in establishing and strengthening NITAGs: Lessons learned from 5 years of the SIVAC initiative. Issue 5 (29th January 2015) - Adjagba, Alex; Senouci, Kamel; Biellik, Robin; Batmunkh, Nyambat; Faye, Pape Coumba; Durupt, Antoine; Gessner, Bradford D.; da Silva, Alfred
Abstract To empower governments to formulate rational policies without pressure from any group, and to increase the use of evidence-based decision-making to adapt global recommendations on immunization to their local context, the WHO has recommended on multiple occasions that countries should establish National Immunization Technical Advisory Groups (NITAGs). The World Health Assembly (WHA) reinforced those recommendations in 2012 when Member States endorsed the Decade of Vaccines Global Vaccine Action Plan (GVAP). NITAGs are multidisciplinary groups of national experts responsible for providing independent, evidence-informed advice to health authorities on all policy-related issues for all vaccines across all populations. In 2012, according to the WHO–UNICEF Joint Reporting Form, among 57 countries eligible for immunization program financial support from the GAVI Alliance, only 9 reported having a functional NITAG. Since 2008, the Supporting Independent Immunization and Vaccine Advisory Committees (SIVAC) Initiative (at the Agence de Médecine Préventive or AMP) in close collaboration with the WHO and other partners has been working to accelerate and systematize the establishment of NITAGs in low- and middle-income countries. In addition to providing direct support to countries to establish advisory groups, the initiative also supports existing NITAGs to strengthen their capacity in the use of evidence-based processes for decision-making aligned with international standards. After 5 years of implementation and based on lessons learned, we recommend that future efforts should target both expanding new NITAGs and strengthening existing NITAGs in individual countries, along three strategic lines: (i) reinforce NITAG institutional integration to promote sustainability and credibility, (ii) build technical capacity within NITAG secretariats and evaluate NITAG performance, and (iii) increase networking and regional collaborations. These should be done through the development and dissemination of tools and guidelines, and information through a variety of adapted mechanisms.